2017
DOI: 10.1002/ece3.3154
|View full text |Cite
|
Sign up to set email alerts
|

Substantial variation in the timing of pollen production reduces reproductive synchrony between distant populations ofPinus sylvestrisL. in Scotland

Abstract: The ability of a population to genetically adapt to a changing environment is contingent not only on the level of existing genetic variation within that population, but also on the gene flow received from differently adapted populations. Effective pollen‐mediated gene flow among plant populations requires synchrony of flowering. Therefore differences in timing of flowering among genetically divergent populations may reduce their ability to adapt to environmental change. To determine whether gene flow among dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 64 publications
(100 reference statements)
1
19
0
Order By: Relevance
“…Driven by the meteorological conditions, sap flux rates were higher in May–August than in April and September. The sap flux in April and September would be consistent with these 2 months being in the early and late period of annual growth of Scots pine (Martínez‐Sancho, Dorado‐Liñán, Hacke, Seidel, & Menzel, ; Whittet, Cavers, Cottrell, Rosique‐Esplugas, & Ennos, ). May in this year had relatively low precipitation input (~37 mm), which potentially limited the replenishment of root‐zone soil moisture.…”
Section: Discussionsupporting
confidence: 62%
“…Driven by the meteorological conditions, sap flux rates were higher in May–August than in April and September. The sap flux in April and September would be consistent with these 2 months being in the early and late period of annual growth of Scots pine (Martínez‐Sancho, Dorado‐Liñán, Hacke, Seidel, & Menzel, ; Whittet, Cavers, Cottrell, Rosique‐Esplugas, & Ennos, ). May in this year had relatively low precipitation input (~37 mm), which potentially limited the replenishment of root‐zone soil moisture.…”
Section: Discussionsupporting
confidence: 62%
“…The extent of local adaptation is dependent upon the strength of differential selection relative to the homogenizing effects of gene flow (Kawecki & Ebert, ). Scots pine is wind‐pollinated, enabling reproduction across large distances; however, in Scotland, it has been shown that asynchrony in flowering phenology may serve to inhibit gene flow among populations (Whittet, Cavers, Cottrell, Rosique‐Esplugas, & Ennos, ). Related work on needle anatomical traits has shown differentiation for stomatal band and resin canal densities, consistent with adaptation to the same longitudinal rainfall gradient that generates adaptive differences in flood tolerance in P. sylvestris in Scotland, is also modest (Donnelly et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Scots pine is wind-pollinated, enabling reproduction across large distances; however, in Scotland, it has been shown that asynchrony in flowering phenology may serve to inhibit gene flow among populations (Whittet, Cavers, Cottrell, Rosique-Esplugas, & Ennos, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is a biologically meaningful climate variable as it reflects the required heat sum associated with the onset of growth (Beaubien and Hamann 2011). It is predicted to be particularly sensitive to climate change (McGinn and Shepherd 2003) as shifts in DD5 for spring perennials, such as Geum triflorum, may have substantial influence on the timing and duration of the growing season (Beaubien and Hamann 2011;Whittet et al 2017). Note: we also ran our analyses with the precipitation variables that loaded highly on PC2, however the results were rarely significant.…”
Section: Climatementioning
confidence: 99%